Analisis Model Pembelajaran Snowball Throwing pada Mata Pelajaran IPS Siswa Kelas I di SDN Ngujung 2 - Marsini Marsini (Mahesa Research Center, 2023)
The purpose of this study was to analyze how the snowball throwing learning model was applied to social studies subjects of grade IV students at SDN ngujung 2. The approach used is a qualitative approach with a descriptive type. The data collection technique uses observation, interview, and documentation techniques. The results showed that the application of the Snowball Throwing learning model was able to increase student learning activity in social science subjects. In social science subjects, students have a fairly good activeness in the process of teaching and learning activities. Students are involved physically and mentally in the learning process such as asking questions, asking opinions, doing assignments, and discussing. Increasing student learning activity is in accordance with student learning activity indicators, namely participating in carrying out learning tasks, being involved in solving a problem, asking friends or teachers for example there is material that is not understood, trying to find information as problem solving, carrying out group discussions, measuring the abilities and results that have been obtained, practicing in solving a problem, applying the learning results obtained in solving Problems Faced. The obstacles faced are such as the duration of learning time is lacking, classrooms that are less strategic, and interference from ignorant friends.